Deep degasion and oil-and-gas containment of the Eastern (Ukrainian) Carpathians: geodynamic and geothermal aspects - Р.І. Кутас (Геофизический журнал, 2022)
The article presents the results of comprehensive analysis of geodynamic conditions, geothermal regime, distribution of oil-and-gas deposits, as well as degassing of Earth’s crust in the Ukrainian sector of the Eastern Carpathians, being a part of the Carpathian petroliferous province. Within the boundaries of the Ukrainian sector of the Carpathians, three main tectonic units are distinguished: the Pre-Carpathian Foredeep, the Folded Carpathians, and the Transcarpathian Trough. Each of them consists of several zones or tectonic covers. Oil-and-gas deposits are mainly concentrated within the Pre-Carpathian Foredeep. Gas deposits prevail in its outer zone, while the oil deposits in inner one. Seve-ral small methane deposits were discovered in the Transcarpathian Trough, and only one deposit in the Folded Carpathians.Earth’s crust within the whole Carpathian region is characterized by high level of gas saturation. Here methane and carbon dioxide prevail. According to chemical composition of gas and isotopic signature of carbon in carbonaceous gases, two areas can be distinguished within the region: north-east, where methane dominates, and south-west, where carbon dioxide prevails. These areas are divided by the Central Carpathian tectonic zone. They adhere to geothermal zoning. The former is characterized by low geothermal activity (heat flow density is 35—60 mW/m2), and the latter — by high level activity (heat flow density exceeds 70 mW/m2).